Passive stability enhancement with sails of a hovering flapping twin-wing robot. (April 2019) - Altartouri, H; Roshanbin, A; Andreolli, G; Fazzi, L; Karásek, M; Lalami, M; Preumont, A
Hovering flapping wing flight is intrinsically unstable in most cases and requires active flight stabilization mechanisms. This paper explores the passive stability enhancement with the addition of top and bottom sails, and the capability to predict the stability from a very simple model decoupling the roll and pitch axes. The various parameters involved in the dynamical model are evaluated from experiments. One of the findings is that the damping coefficient of a bottom sail (located in the flow induced by the flapping wings) is significantly larger than that of a top sail. Flight experiments have been conducted on a flapping wing robot of the size of a hummingbird with sails of various sizes and the observations regarding the flight stability correlate quite well with the predictions of the dynamical model. Twelve out of 13 flight experiments are in agreement with stability predictions.